Contraceptive access and use before and during the COVID-19 pandemic: a mixed-methods study in South Africa and Zambia [version 2; peer review: 1 approved, 2 approved with reservations] - Cecilia Milford; Alice F. Cartwright; Margaret Kasaro; Rebecca L. Callahan; Christina Wong; Jennifer H. Tang; Virginia Maphumulo; Marissa Velarde; Manze Chinyama; Maria Fawzy; Mayaba Mudenda; Esther Chabu; et al. (Gates Open Research, 2024)
Background The COVID-19 pandemic affected global access to health services, including contraception We sought to explore effects of the pandemic on family planning (FP) service provision and use in South Africa and Zambia, including on implant and intrauterine device (IUD) users’ desire and ability to obtain removal. Methods Between August 2020 and April 2021, we conducted surveys with 537 women participating in an ongoing longitudinal contraceptive continuation study. We also carried out in-depth interviews with 39 of the survey participants and 36 key informants involved in FP provision. We conducted descriptive analysis of survey responses and thematic analysis of interviews. Results Contraceptive use changed minimally in this sample with the emergence of COVID-19. Fewer than half of women (n=220) reported that they tried to access FP since the start of the pandemic. The vast majority of those seeking services were using short-acting methods and 95% were able to obtain their preferred method. The proportion of women not using a method before and after the start of the pandemic did not change in Zambia (31%), and increased from 8% to 10% in South Africa. Less than 7% of implant or IUD users in either country reported wanting removal. Among the 22 who sought removal, 10 in Zambia and 6 in South Africa successfully obtained removal. In qualitative interviews, those reporting challenges to service access specifically mentioned long queues, deprioritization of contraceptive services, lack of transportation, stock-outs, and fear of contracting COVID-19 at a facility. Key informants reported stock-outs, especially of injectables, and staff shortages as barriers. Conclusions We did not find a substantial impact of COVID-19 on contraceptive access and use among this sample; however, providers and others involved in service provision identified risks to continuity of care. As the COVID-19 pandemic wanes, it continues to be important to monitor people’s ability to access their preferred contraceptive methods.